PERENCANAAN PENINGKATAN FLOOD SHELTER DI DAERAH ALIRAN SUNGAI BERINGIN SEMARANG - Siti Nuriskha Amalia; Annisa Khizamatul F. Utami; Suharyanto Suharyanto; Dwi Kurniani (Jurnal Karya Teknik Sipil, 2014)
Flood is one of the disaster which often happened in Semarang city. Many negative impact arising from flood disaster, such as loss of victim or material. One of the handling solution is  developed flood shelter. Some region of Semarang cityhave own flood shelter, so in this case we need to identify of elegibility and improvement. Identification location of flood shelter are in Beringin Watershed Semarang which consists of 6 Kelurahan, namely Kelurahan Wates, Kelurahan Wonosari, Kelurahan Mangunharjo, Kelurahan Mangkang Wetan, Kelurahan Gondorio, and Kelurahan Beringin. Data obtained from the field survey,with existing data of flood shelter that has been there. Sources of criteria for  flood shelter location are sphere project handbook, 2011, Health Minister’s decision on the minimum sandart of health problems caused by disaster prevention and handling of refugees, and egulations of BPBD. Some regions like Sub-District of Wonosari require a building in the form of House Podium and emergency doorstep. Because the location have bank- bank resulting the pursuing of evacuating and handling. Besides, some shelter pitched a tent of the size according to requirement to accomodate lacking of room for refugee in shelter. But, people arround the riverbanks should keep the environment clean and not littering, so can decrease the impact of flood.